Sclerotherapy in venous malformation. (March 2013) - Rabe, E; Pannier, F
Venous malformations are the result of an arrested development of the venous system during the embryogenesis. In the treatment of venous malformations the standard of care is a multidisciplinary approach including the use of traditional surgical therapy if applicable and endovascular treatment. Endovascular techniques include embolization therapy for instance with coils but also sclerotherapy with liquid or foamed sclerosants. The aim of this paper is to give an overview of foam sclerotherapy in venous malformations. Sclerotherapy of venous malformations has been performed in superficial and intramuscular malformations. In many cases ethanol has been used for the treatment. Since more than 10 years, less aggressive sclerosants like polidocanol and sodiumtetradecyl sulphate have been used to treat venous malformations. These substances can be used without anaesthesia and the rate of side-effects is much lower. Yamaki and Cabrera are the first who used foam sclerotherapy for the treatment of symptomatic venous malformations. Compared with liquid sclerotherapy foam sclerotherapy has the advantage of a better and longer lasting contact of the sclerosing agent with the vessel wall which leads to a more effective treatment and to a reduction of concentrations needed. In a recent European Guideline on Sclerotherapy foam sclerotherapy is recommended over liquid therapy for the treatment of venous malformations. Foam sclerotherapy is an effective treatment option for low flow extratruncular and truncular venous malformations. Foam is significantly more effective than liquid sclerotherapy and side-effects with polidocanol or sodiumtetradecyl sulphate foam are less compared with sclerotherapy with ethanol. With foam sclerotherapy a significant reduction of pain and volume of the venous malformations can be reached.